Evidence of Terrain-Induced Windshear Due to Lantau Island over the Third Runway of the Hong Kong International Airport—Examples and Numerical Simulations - Pak Wai Chan; Kai Kwong Lai (Applied Sciences)
The new third runway of the Hong Kong International Airport was commissioned in November 2022. With the increased distance away from the mountains of Lantau Island to its south, it is not certain if terrain-induced windshear could still happen over the corridors of this runway, particularly the usual landing runway corridor (07LA) for aircraft from the west. With the rebound of air traffic in 2024 in Hong Kong, it is now possible to find out the impact of the Lantau terrain on the winds over 07LA, at least based on case studies. It is found that, though 07LA is located at least 4 km from the foothills of Lantau Island, which has peaks rising to about 1 km above mean sea level, the terrain-induced airflow disturbances could, at times, extend to 7–8 km away from the mountains to bring about low-level windshear and turbulence to this runway corridor. This conclusion is drawn based on actual pilot windshear reports and observations from Doppler light detection and ranging (LIDAR) systems and confirmed by simulations using a mesoscale to microscale numerical weather-prediction model. It is consistent with the definition of open terrain for a height-over-distance ratio of 1:10. Based on the experience in Hong Kong, it is found that, for runway corridors located at distances within 10 times the height of the nearby terrain, it is still necessary to set up windshear detection equipment, such as Doppler LIDAR, to safeguard aircraft operation.